Enhancing Elementary School Students' Mathematical Comprehension Through Innovative Technology-Assisted Learning - Rospita Panjaitan; Ester Julinda Simarmata; Rosdiana Samosir (Departement of Mathematics Education, 2024)
This project analyzes the adoption of technology-assisted learning in primary school mathematics, notably focusing on the issue of two-dimensional forms. The study explores the efficiency of deploying Macromedia Flash as a learning tool and its effects on students' mathematical understanding. A complete study was undertaken, considering pre-test and post-test scores, as well as feedback from both teachers and students. The data demonstrate a significant improvement in students' mathematics comprehension, with an average rise of 18.52 in the field trial and 21 in the dispersion test. These results demonstrate that Macromedia Flash-supported learning is a strong way to boost students' knowledge of mathematical concepts. The moderate to high levels of improvement show that the employment of this media positively adds to students' academic success. Moreover, the favorable responses from both teachers and students underline the acceptance and enthusiasm toward this technology-based learning innovation. The high degree of student satisfaction, with an average score above 87.6, suggests that Macromedia Flash not only boosts motivation but also produces an enjoyable learning environment. In conclusion, this study offers promising prospects for the development and application of technology-assisted learning in primary school mathematics. The development in pupils' mathematics understanding extends beyond cognitive elements, incorporating critical thinking skills and problem-solving ability. Thus, this research contributes to the ongoing efforts to enhance the quality of mathematics teaching at the primary level through the appropriate integration of learning technology.